Insider Ownership and the Value of the Bucharest Stock Exchange Listed Companies: Convergence-of-Interest or Entrenchment Effect? - Vintila, Georgeta; Gherghina, Stefan Cristian (International Journal of Economics and Financial Issues, 2013)
The aim of this paper is to provide empirical evidence regarding the effect of insider ownership on firm value which stems from the lack of such study for the case of Romania. By using a sample of companies listed on the Bucharest Stock Exchange, over the period 2007-2011, our results showed a negative effect of insider shareholdings on firm value. Likewise, the negative effect on firm value was confirmed for insider ownership one-year lagged. Thereby, unconcerned to the level of shareholdings, we ascertained the entrenchment effect, opposite to the goal of shareholders wealth maximization. Keywords: corporate governance; agency theory; insider ownership; firm value; panel data regression models JEL Classifications: G32; G34 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->